Spirituality and Suicidality Among Patients with Schizophrenia: A Cross-sectional Study from Nigeria (2021)
Studies which have explored the effect of spirituality on suicidality among patients with schizophrenia have been characterized by inconsistent results. The aim of this study was to examine the relationship between spirituality and suicidality among stable patients with schizophrenia in Nigeria. The Daily Spiritual Experience Scale was applied to measure spirituality. There was found a significant relationship between spirituality and having had suicidal thoughts in a lifetime. Spirituality was negatively correlated with the severity of negative symptoms, total positive and negative syndrome scale score (PANSS), the severity of depression, and positively correlated with functioning.